Constant properties of plant–frugivore networks despite fluctuations in fruit and bird communities in space and time. Issue 6 (1st June 2013) - Plein, Michaela; Längsfeld, Laura; Neuschulz, Eike Lena; Schultheiß, Christina; Ingmann, Lili; Töpfer, Till; Böhning-Gaese, Katrin; Schleuning, Matthias
Abstract : Human‐induced changes in anthropogenic landscapes are a predominant threat to biodiversity and have been documented to affect mutualistic interactions between plants and animals, such as avian seed dispersal. Interactions between fleshy‐fruited plants and frugivorous birds are highly seasonal in temperate ecosystems. Nevertheless, combined effects of landscape modification and seasonal variation on plant–frugivore interactions have never been assessed from a network perspective. Here, we present the first study that simultaneously investigates effects of landscape modification and seasonal variation on plant–frugivore interactions and on functional and interaction diversity of plant–frugivore networks. We recorded visitation rates of 39 frugivorous bird species to 28 fruiting‐plant species in Central Germany from early summer to late autumn in hedgerows within three landscape types arranged along a gradient of decreasing anthropogenic modification and increasing structural diversity (i.e., farmland, orchard, forest edge). We analyzed how species richness, abundance, and community composition, as well as functional and interaction diversity of fruiting plants and frugivorous birds changed with landscape type, fruit availability, and season. We found that visitation rates of frugivorous birds were lower in farmland, but only in summer. In autumn, visitation rates were similar in all landscape types and strongly increased with increasing local fruit availability. The functional diversity of fruits and frugivorous birds and their interaction diversity remained surprisingly constant in all landscape types. Due to seasonal changes in communities of fruiting plants and frugivorous birds, functional dispersion of fruiting plants was lower in autumn than in summer, whereas functional richness and dispersion of frugivorous birds was higher in autumn than in summer. Our results indicate that seasonal changes in fruit availability influence the abundance of frugivorous birds along gradients of structural diversity at the landscape scale. Although seasonal fluctuations influenced the functional diversity of avian frugivore communities, we found constant interaction diversity of plant–frugivore networks in space and time, probably due to the functional redundancy of frugivorous birds. These findings indicate a high robustness of avian frugivory to moderate levels of human‐induced landscape modification in temperate ecosystems and call for studies testing the generality of these findings for ultimate avian seed dispersal functions.